Genetic variants of hepatitis B virus in patients with chronic hepatitis B - E. A. Elpaeva; O. E. Nikitina; M. M. Pisareva; I. V. Shilova; V. A. Greshnjakova; M. P. Grudinin; O. I. Kiselev (Журнал инфектологии, 2015)
Introduction. Biological properties of virus, such as susceptibility to antivirals, the clinical course of chronic hepatitis B (CHB), the probability of developing cirrhosis and hepatocellular carcinoma are determined by genotype and mutations in the genome of the hepatitis B virus (HBV).The aim of the study was evaluating of HBV genetic variants in patients with CHB from St. Petersburg hospitals.Material and methods. A total of 1414 CHB patients with positive polymerase chain reaction HBV genome in blood and/or liver tissue were observed. Genotype was determined in 298 patients, sequencing of the polymerase gene fragment was performed in 80 patients.Results. Viral DNA was detected in 323 (55.8%) patients with CHB. Genotype D was determined in 238 (80,1%), genotype A – in 49 (16,5%), C genotype – in 2 (0,7%) and mixed A+D – in 8 (2,7%) patients. Substitutions in YMDD-motif of the polymerase protein (M204I/V) as well as other primary and secondary resistance mutations to nucleotide analogues (lamivudine, telbivudine, entecavir) were found in four patients. Mutations in the reverse transcriptase (rt) region of polymerase gene were shown to affect the structure of surface protein. The substitution rtA181T in three patients resulted in formation of stop codon (sW172*) and premature termination of surface protein synthesis. The absence of HBeAg and the degree of fibrosis increase in 7 patients may be the result of mutations identified in core gene (G1896A, A1762T, G1764A).Conclusion. Study of the geographical distribution of HBV genotypes and identification of amino acid substitutions leading to decrease in serum markers concentration and emergence of resistance antivirals mutations is of great practical importance for predicting severity of the disease and effectiveness of antiviral therapy.